(untitled) (Perner’s Contacts, 2008)
In this article are described experiences of Department of Technical Sciences and Informatics (next KTVI) focused on scientific research activities and international cooperation for last five years. The KTVI which is a part of Faculty of Special Engineering and the University of Zilina were processed national as well as international projects. Gained financial support was used for development of cooperation with partner institutions in Bulgaria, Czech Republic, Poland, Serbia and to provide technical maintenance of department.